Georgia Public Expenditure Review : Building a Sustainable Future - World Bank (Washington, DC, 2017)
This Public Expenditure Review (PER) was prepared at the request of the Ministry of Finance of Georgia; its analysis of public spending is designed to inform the Georgian authorities on the fiscal policies that support growth and equity. As Georgia strives to meet the challenges of a fluid global economic environment, this PER is intended to support the government’s efforts to secure macroeconomic and fiscal sustainability to promote growth and equity. This is a testing time for Georgia’s public finances, as the country faces slowing growth and a difficult regional context.This Public Expenditure Review (PER) is organized in two chapters; the first focusing on the overarching macro-fiscal challenges facing Georgia, and the second “zooming in” to the challenges for public spending in the health sector. In particular, the PER provides an overview of the recent macroeconomic and fiscal developments highlighting major drivers of rising spending, and analyzes potential revenue gains that could be derived from eliminating tax expenditures (Chapter 1). The second part of the report carries out a detailed review of the health spending in Georgia, providing both the context and rationale for implementing the much needed Universal Healthcare (UHC) program in 2013, while highlighting the need for properly managing the existing short-term cost pressures, as well further improving the system’s long-term efficiency and sustainability. This PER is an integral part of the programmatic series of PERs (2012, 2014, and 2015) providing new analyses and recommendations that are complementary to the existing ones. The PER (2012) analyzed the rising expenditure pressures on social and capital spending, and presented options for fiscal consolidation, including measures to improve selectivity in capital expenditures, enhance the sustainability of the pension program, and the coverage of targeted social assistance. The PER (2014) examined the spending on social protection, health, and education, and provided recommendations including strengthening the Social Service Agency, increasing the UHC drug coverage, strengthening preschool education, and improving general and vocational education. It also analyzed quasi-fiscal spending and intergovernmental fiscal relations. A special volume of the PER (2014) studied Georgia’s Public Investment Management and how it could be further enhanced to improve the efficiency of public investment. The PER (2015) highlighted the presence of spending pressures from social programs and analyzed spending efficiency, which led to policy options to direct the redistribution policies towards greater equity, improve agriculture subsidy programs and local government spending.This PER, as a continuation of the series, while focusing its analyses and recommendations strategically on new and specific challenges, it also draws a selected number of recommendations from previous PERs, notwithstanding that most issues covered in previous PERs remain crucial and need to be addressed in parallel.